Pada ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EKSPOR KARET INDONESIA KE JEPANG (2002-2022): Ekspor Karet Indonesia ke Jepang - Alvian Priambudi (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
Indonesia is the second largest rubber producing country in the world. The rubber plant is a prima donna commodity from the non-oil and gas sector which has a high export value. Japan is a country that requires a lot of raw material supplies for the automotive industry from Indonesia. This study aims to analyze the factors that affect Indonesia's rubber exports to Japan from 2002 to 2022. This study uses quantitative methods with multiple linear regression analysis using classical assumption tests and hypothesis testing. The data used in this study comes from the Directorate General of Plantations (Ditjenbun), the Central Statistics Agency (BPS), and the World Bank and uses secondary data that is time series. This study found the results that Land Area has a significant and positive influence on Indonesian Rubber Exports to Japan, Total Production has a significant and positive influence on Indonesian Rubber Exports to Japan, Exchange Rate has no significant and negative influence on Indonesian Rubber Exports to Japan, and International Rubber Prices have no significant and negative influence on Indonesian Rubber Exports to Japan.